3D-printed nanocomposite scaffolds with tunable magnesium ionic microenvironment induce in situ bone tissue regeneration. (September 2019) - Shen, Jie; Wang, Wenhao; Zhai, Xinyun; Chen, Bo; Qiao, Wei; Li, Wan; Li, Penghui; Zhao, Ying; Meng, Yuan; Qian, Shi; Liu, Xuanyong; Chu, Paul K.; et al.
Graphical abstract: Highlights: Tunable magnesium ionic 3D microenvironments were realized by using nanocomposites comprising of polycaprolactone-co-poly(ethylene glycol)-co-polycaprolactone and surface-modified magnesium oxide nanoparticles. Nanocomposite with the optimal magnesium ionic microenvironment promotes cell viability osteogenic differentiation properties in vitro and superior bone formation in vivo. Compromised osteogenic differentiation and bone tissue regeneration capabilities were shown in the sample of nanocomposite with excessive magnesium ionic microenvironment. Abstract: Local tissue microenvironment is able to regulate cell-to-cell interaction that leads to effective tissue repair. This study aims to demonstrate a tunable magnesium ionic (Mg 2+ ) microenvironment in bony tissue that can significantly induce bone defect repair. The concept can be realized by using a newly fabricated nanocomposite comprising of custom-made copolymer polycaprolactone-co-poly(ethylene glycol)-co-polycaprolactone (PCL-PEG-PCL) and surface-modified magnesium oxide (MgO) nanoparticles. In this study, additive manufacturing (AM) technology had been adopted to help design the porous three-dimensional (3D) scaffolds with tunable Mg 2+ microenvironment. We found that the wettability and printability of new copolymer had been improved as compared with that of PCL polymer. Additionally, when MgO nanoparticles incorporated into the newly synthesized hydrophilic copolymer matrix, it could lead to increased compressive moduli significantly. In the in vitro studies, the fabricated nanocomposite scaffold with low concentration of Mg 2+ microenvironment not only demonstrated better cytocompatibility, but also remarkably enhanced osteogenic differentiation in vitro as compared with the pure PCL and PCL-PEG-PCL co-polymer controls. In the animal studies, we also found that superior and early bone formation and tissue mineralization could be observed in the same 3D printed scaffold. However, the nanocomposite scaffold with high concentration of Mg 2+ jeopardized the in situ bony tissue regeneration capability due to excessive magnesium ions in bone tissue microenvironment. Lastly, this study demonstrates that the nanocomposite 3D scaffold with controlled magnesium concentration in bone tissue microenvironment can effectively promote bone defect repair.